Development of Stabilized and Aqueous Dissolvable Nanosuspension Encompassing BCS Class IV Drug via Optimization of Process and Formulation Variables - Goel, Surya; Agarwal, Vijay; Sachdeva, Monika (Recent Patents on Nanotechnology, 2026)
BackgroundNanosuspension has emerged as an effective, lucrative, and unequalled approach for efficiently elevating the dissolution and bioavailability of aqueous soluble drugs. Diverse challenges persist within this domain, demanding further comprehensive investigation and exploration.ObjectiveThis study aims to design, develop, optimise formulation and process variables, and characterise the stabilised aqueous dissolvable nanosuspension using chlorthalidone as a BCS class-IV drug.MethodsNanosuspensions of the chlorthalidone drug were prepared using a combination of top-down and bottom-up approaches. Various polymers such as Pluronic L-64, F-68, F-127, and Synperonic F-108 were used as stabilisers in this research. All important processes and formulation variables, such as ultrasonication intensity and time, the concentration of the drug, organic solvent, and stabilisers that may critically influence the characteristics of the nanosuspensions, were optimised. Formulation screening was performed using the optimisation of process and formulation variables, and the optimised nanosuspension formulation was assessed for particle size, PDI, surface charge, morphology, in vitro drug release, and stability.ResultsTo select an optimised nanosuspension formulation, the effects of formulation and process variables were investigated. These variables critically influence the development of a stabilised nanosuspension. The outcomes revealed that the nanosuspension formulation containing pluronic F-68 as a stabiliser in 0.6% w/v concentration and the drug in 4 mg/ml concentration were optimized. The particle size and zeta potential of the optimised preparation were 110 nm and -27.5 mV, respectively. The in-vitro drug release of chlorthalidone drug from the optimised nanoformulation was increased up to 3-fold, approximately (88% in 90 min) compared with pure chlorthalidone drug (27% in 90 min) because of the decrease in particle size. Moreover, stability studies indicated that the crafted nanoformulation was stable at cold (4°C) as well as normal room temperature (25°C) for six months.ConclusionFrom the obtained results, it was concluded that the combination of top-down and bottom-up approaches employed for the fabrication of oral nanosuspension is a remunerative and lucrative approach to successfully resolve the perplexities associated with the dissolution rate of poorly aqueous soluble BCS class-IV drug moieties such as chlorthalidone. Moreover, various patents have been granted over this novel technology which have also summarized in the manuscript for the better understanding of readers.
Keywords: drug release